Provision of academic data for research: a step for academic success - Miguel, H. (2020)
One of the most widely researched issue on higher education relates to exposed paths that lead to academic success. Nowadays information systems represent an essential part of the education sector in many universities. In particular, the increasing of the number of students in higher education in Portugal leads to the progressive increase of student’s data contained in institutional information systems. This article aims to include the use of student data contained in the Fénix information system of a Portuguese higher educational institution, turning their information in an internal tool, to assist analysis and studies of internal academic success. Providing relevant data for queries can offer a clearer explanation of the paths to success in higher education. It can also help the identification of problems and failures aiming to support a more effective intervention of institutions and researchers to improve the academic success.